Utilization of limestone powder and fly ash in blended cement: Rheology, strength and hydration characteristics. (30th January 2020) - Jiang, Dongbing; Li, Xiangguo; Lv, Yang; Zhou, Mingkai; He, Chenhao; Jiang, Wenguang; Liu, Zhuolin; Li, Changjiao
Highlights: LS decreases the fluidity of blended cement containing FA. LS can promote the hydration of cement and FA. The synergistic effect of LS with FA is beneficial for the strength development. Abstract: The objective of this study was to assess the utilization feasibility of limestone powder (LS) and fly ash (FA) for the preparation of blended cement, and provide an optimum proportion. In this work, LS and FA were used to replace part of cement at 30% by mass. The effect of LS and FA on the rheology, fluidity and mechanical properties of the blended cement were investigated. The hydration process, hydration products and microstructure were analyzed with differential scanning calorimetry (DSC), X-ray diffraction (XRD), thermogravimetry analyses (TGA), nuclear magnetic resonance (NMR), and scanning electron microscopy (SEM). Results demonstrated that the addition of LS increased the yield stress and plastic viscosity of OPC-FA-LS pastes and decreased the fluidity of mortars, due to its fine particle size. LS could accelerate the hydration rate of cement, improve the hydration degree of cement (RC ), and lead to a denser structure due to its filling effect at early age. In addition, FA consumed a large amount of CH and formed denser C-S-H at late age, and its hydration degree (RFA ) could be also promoted by LS. The results confirmed that the utilization of LS and FA could synergistically promote the hydration of cement, and was beneficial for the strength development of blended cement. The optimum proportion of LS and FA used to replace cement was 10% and 20%, which could provide useful experience for the utilization of LS and FA in engineering application.